(untitled) (Journal of Enam Medical College, 2024)
Background: In present days, laparoscopic cholecystectomy is the gold standard technique for the treatment of gallstone diseases. Effective pain control is an essential component for the patients during postoperative period. Objectives: The aim of this study was to evaluate the effects of port site infiltration of local anesthetics (Inj. 0.5% bupivacaine) in reduction of pain and opioid usages during postoperative period following laparoscopic cholecystectomy. Materials and Methods: A randomized control trial prospective analytical study was conducted in the department of Anesthesiology of Enam Medical College & Hospital in Bangladesh. The patients subjected to laparoscopic cholecystectomy were the study population. Total 60 patients were selected and randomly allocated into two groups as “control group” and “study group”. Study group assigned to receive 0.5% bupivacaine at port sites. The evaluation of postoperative pain was done according to the numeric pain rating scale. Data regarding percentage of analgesic consumed and duration of hospital stay were recorded and analyzed. Results: The mean age of the patients in control group was 44.26±15.56 years and in study group 38.50±12.87 years (p=0.20). Mean weight of the patients was 61.13±8.25 kg in control group and 59.33±8.27 kg in study group (p=0.09). Male female ratio in control group was 11:19 and 8:22 in study group. Mean pain score at 4 hours was significantly lower in the study group compared to control group. Additional analgesics were required 86% in control group and 47% in study group. The mean duration of hospital stay in control group and study group was 2.6 days and 1.6 days respectively. Conclusion: Infiltration of bupivacaine into port sites is simple, inexpensive, and effective technique to reduce postoperative pain and opioid requirements. It can be conventionally practiced for laparoscopic cholecystectomy operation. J Enam Med Col 2021; 11(3): 180−184